The 'Roxolany Tephra' (Ukraine) − new evidence for an origin from Ciomadul volcano, East Carpathians. (12th August 2016) - Wulf, Sabine; Fedorowicz, Stanisław; Veres, Daniel; Łanczont, Maria; Karátson, Dávid; Gertisser, Ralf; Bormann, Marc; Magyari, Enikö; Appelt, Oona; Hambach, Ulrich; Gozhyk, Petro F.
ABSTRACT: We present major element glass data and correlations for the 'Roxolany Tephra' − a so far geochemically unconstrained volcanic ash layer previously described in last glacial (Marine Isotope Stage 2) loess deposits of the Roxolany loess–palaeosol complex in south‐west Ukraine. This exceptionally well‐preserved, 2–3‐cm‐thick tephra layer is characterized by a rhyolitic glass composition that is comparable to that of proximal tephra units from Ciomadul volcano in the East Carpathians, central Romania. The chemistry particularly matches that of the final Latest St. Ana Phreatomagmatic Activity pyroclastic fall unit of St. Ana crater that is radiocarbon dated in the proximal Mohoş coring site (MOH‐2) to 29.6 ± 0.62 cal ka BP. The age of the tephra correlative agrees with the newest radiocarbon and infrared optically stimulated luminescence age constraints from overlying palaeosols and tephra‐embedding loess of the Roxolany sequence, respectively, which place the tephra between ca. 33 and 24 cal ka BP, and thus confirm the long‐debated chronostratigraphy of this important environmental archive. The occurrence of a distal Ciomadul tephra ca. 350 km east of its source indicates great potential for further tephra and cryptotephra findings from this volcanic complex in the south‐eastern Mediterranean and Black Sea region.